MODEL PENGUATAN BUDI PEKERTI PESERTA DIDIK MELALUI PENGEMBANGAN EMPATI DI SMP NEGERI 3 MREBET - Priyanto (CV. Amerta Media, 2017)
One way to lay the foundation of character education is to develop and nurture the empathy of children from an early age. With the growth and development of empathy in children from an early age will affect the development of the character / personality and behavior of children as adults. According to Goleman (1997), the roots of empathy have existed in a person since they were babies or since they were born. The development of empathy when a baby is strongly influenced mother on the baby. The absence of a parent between the child and the child will harm the child's emotions and may collect the empathy of the child. In school education, the teacher can do the penyetalaan by synchronizing emotions with their students. In Junior High School 3 Mrebet Purbalingga District, empathy can be grown and developed in children with various approaches, among others: the existence, the story / moral story, the use of verbal words, direct experience, togetherness of play, and habituation.Key Words: manners, development of empathy